Genomic insights into the Ixodes scapularis tick vector of Lyme disease - Gulia-Nuss, Monika; Nuss, Andrew B.; Meyer, Jason M.; Sonenshine, Daniel E.; Roe, R. Michael; Waterhouse, Robert M.; Sattelle, David B.; Fuente, José de la; Ribeiro, José Marcos Chaves; Megy, Karine; Thimmapuram, Jyothi; Miller, Jason R.; et al. (Springer, 2016)
Ticks transmit more pathogens to humans and animals than any other arthropod. We describe the 2.1 Gbp nuclear genome of the tick, Ixodes scapularis (Say), which vectors pathogens that cause Lyme disease, human granulocytic anaplasmosis, babesiosis and other diseases. The large genome reflects accumulation of repetitive DNA, new lineages of retro-transposons, and gene architecture patterns resembling ancient metazoans rather than pancrustaceans. Annotation of scaffolds representing ∼57% of the genome, reveals 20,486 protein-coding genes and expansions of gene families associated with tick–host interactions. We report insights from genome analyses into parasitic processes unique to ticks, including host ‘questing’, prolonged feeding, cuticle synthesis, blood meal concentration, novel methods of haemoglobin digestion, haem detoxification, vitellogenesis and prolonged off-host survival. We identify proteins associated with the agent of human granulocytic anaplasmosis, an emerging disease, and the encephalitis-causing Langat virus, and a population structure correlated to life-history traits and transmission of the Lyme disease agent.